A quality systems study of Benguet Management Corporation - Dimaano, Jed P. (College of Engineering, 1996)
This paper is a documentation of a quality audit system made on Benguet Management Corporation - Foundry Division. Survey was done using the Quality Function Evaluation questionnaire. A quality audit checks an existing quality system against an ideal or objective quality system. The quality system audit results to some improvement areas where the company can adjust on. BMC-FD quality system was studied to be a corrective quality system rather that preventive. The system lacks statistical quality techniques and data gathering procedures. There is also a deficiency in implementation of quality programs and procedures which should always be the initial step before appropriate quality programs are to be implemented in the system. It is therefore recommended that certain strategic programs and activities in the form of seminars, be organized in order to inculcate in management the value of these quality programs and procedures. The installation of a Quality Assurance department would follow after management's dedication and commitment have already been assured.